Predictive Cahce Management - Baltaoğlu, Olcay Gürsel (MEF Üniversitesi, Fen Bilimleri Enstitüsü, 2017)
Major dependency of a mobile application performance is the response time of backend services. Building a cache layer can be a solution in architectural way to provide better experience to user but it cannot affects when the cache is empty for the first usages.
Öngörüsel önbellek yönetimi
Keywords: Cache Management; Predict; Mobile Application; Faster Response Time; Ön Bellek Yönetimi; Mobil Uygulama; Kullanıcı Kullanım Öngörüleri